Mapping Research Trends in the Disaster Resilient Village Program: A Bibliometric Approach and Scientific Visualization Analysis ⁠ - Hj. Aidah.S; Marsuki (P3M Stia Al Gazali Barru and Meraja media, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal